DEVELOPMENT OF NITRITE ANALYSIS METHOD IN PROCESSED CHEESE PRODUCTS USING UV - VIS SPECTROPHOTOMETRY - Al Amin Refnaldi, Ihsan
Food additives (FA) are ingredients added to food to affect the nature or form of food. Meanwhile, nitrite is one of the FA that belongs to the preservative functional class permitted to be added into several categories of food products, including processed cheese products. This study aims to obtain an analytical method that can be applied for determination of nitrite in these food products. Processed cheese is a food product with a fairly complex matrix so liquid-liquid extraction and precipitation techniques are carried out in sample preparation to separate and minimize matrix interferences. The nitrite present in the sample was acidified and then reacted with sulfanilic acid to form diazonium hydrochloride salt as an intermediate. Furthermore, it was reacted with N-1-naphthyl-ethylenediaminedihydrochloride (NED) to produce a colored product absorbs visible radiation at a maximum wavelength of 550 nm. Method validation was carried out which included determination of linearity, precision, accuracy, limit of detection, and limit of quantization of the method. Nitrites were determined in simulated cheese samples. From the research results, the calibration curve with the equation of Y = 0.6654 X – 0.002 and r2 = 0.9998 within the concentration range of 0.38 to 1.15 ppm was obtained. The precision of the method expressed as relative standard deviation (SBR) was within the range of 0.67 - 6.44 %, while the accuracy of the method expressed as percentage of recovery was within the range of 98.8 – 104.6 %. The detection limits (BD) and quantization limits (BK) methods were 0.01 and 0.02 ppm, respectively. Based on the results obtained, it could be concluded that the method for determining nitrite in processed cheese products has been successfully obtained and can be used for the routine determination of nitrite in these food products.